The Influence of Changing Heat Transfer Coefficient, Type of Fluid, and Pipe Material on the Efficiency of the Distillation Exchanger - Rasul, Hardi Abdulla M.; Barzanjy, Mohammed Jawdat; Aljeware, Hazim Abed Mohammed (International Journal of Membrane Science and Technology, 2023)
The fundamental purpose of the petroleum refining industry is to convert crude oil into refined products comprising more than 2,500 substances. Among the refined products are liquefied petroleum gasoline, aviation fuel, kerosene, fuel oils, diesel fuel, lubricating oils, and feedstocks, which have a variety of uses in the petrochemical and other industries. The petroleum refinery process begins with crude oil storage and continues with handling and refining operations before concluding with the separation process and shipping the refined compounds to their final destinations. A variety of methods are used in the petroleum refinery. The analysis of key components of the oil refinery will have a significant impact on the quality of the distilled products. Several scenarios, such as transfer coefficient, fluid type, and pipe materials, have been simulated to determine the most powerful example for the updated oil refineries, and their consequences are described.